Food allergy and hypersensitivity reactions in children and adults—A review. (22nd December 2021) - Tedner, Sandra G.; Asarnoj, Anna; Thulin, Helena; Westman, Marit; Konradsen, Jon R.; Nilsson, Caroline
Abstract: Adverse reactions after food intake are commonly reported and a cause of concern and anxiety that can lead to a very strict diet. The severity of the reaction can vary depending on the type of food and mechanism, and it is not always easy to disentangle different hypersensitivity diagnoses, which sometimes can exist simultaneously. After a carefully taken medical history, hypersensitivity to food can often be ruled out or suspected. The most common type of allergic reaction is immunoglobulin E (IgE)–mediated food allergy (prevalence 5–10%). Symptoms vary from mild itching, stomach pain, and rash to severe anaphylaxis. The definition of IgE‐mediated food allergy is allergic symptoms combined with specific IgE‐antibodies, and therefore only IgE‐antibodies to suspected allergens should be analyzed. Nowadays, methods of molecular allergology can help with the diagnostic process. The most common allergens are milk and egg in infants, peanut and tree nuts in children, and fish and shellfish in adults. In young children, milk/egg allergy has a good chance to remit, making it important to follow up and reintroduce the food when possible. Other diseases triggered by food are non‐IgE‐mediated food allergy, for example, eosinophilic esophagitis, celiac disease, food protein‐induced enterocolitis syndrome, and hypersensitivity to milk and biogenic amines. Some of the food hypersensitivities dominate in childhood, others are more common in adults. Interesting studies are ongoing regarding the possibilities of treating food hypersensitivity, such as through oral immunotherapy. The purpose of this review was to provide an overview of the most common types of food hypersensitivity reactions. Abstract :